ENGLISH FOR SPECIFIC PURPOSES: NEEDS ASSESSMENT - A. S. Sarsenbayeva; M. S. Kulakhmetova (Вестник Кемеровского государственного университета, 2015)
The paper presents the needs assessment project for ESP course conducted in the framework of «E-teacher Scholarship program». The needs assessment included such aspects as target situation analysis, present situation analysis and context analysis. The needs assessment project is conducted in order to design the syllabus for the students of the specialty “Thermal engineering”. The paper reveals the goals of the discipline “English for specific purposes” for students with account of their professional distinctiveness. The data are taken from the materials collected at students’ questionnaires, observation, interviewing “Thermal engineering” teachers. The paper also considers ESP challenges faced by university teachers. The absence of the placement test, poor English language competence of non-language teachers conducting the lesson, few practical hours influence the quality of material acquisition.